2004
DOI: 10.4049/jimmunol.172.5.3059
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of the Toll-Like/IL-1 Receptor Superfamily to Innate and Adaptive Immunity to Fungal Pathogens In Vivo

Abstract: In vitro studies have indicated the importance of Toll-like receptor (TLR) signaling in response to the fungal pathogens Candida albicans and Aspergillus fumigatus. However, the functional consequences of the complex interplay between fungal morphogenesis and TLR signaling in vivo remain largely undefined. In this study we evaluate the impact of the IL-1R/TLR/myeloid differentiation primary response gene 88 (MyD88)-dependent signaling pathway on the innate and adaptive Th immunities to C. albicans and A. fumig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

35
493
8
15

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 465 publications
(551 citation statements)
references
References 71 publications
35
493
8
15
Order By: Relevance
“…They attribute this to an expansion of the CD4 þ CD25 þ regulatory T-cell population and a decreased macrophage candidacidal capacity in the presence of TLR2. These findings were supported by Bellocchio et al, 78 who found a reduced fungal load in the kidneys of TLR2-deficient mice but no difference in mortality. The reason for the apparently opposing role of TLR2 in controlling the response to systemic candidiasis is unclear, but may reflect differences in the strain of C. albicans used, since TLRs have been shown to discriminate between fungal morphotypes.…”
Section: Deficiencies Of Innate Immunity and Involvement In Early Infsupporting
confidence: 70%
See 1 more Smart Citation
“…They attribute this to an expansion of the CD4 þ CD25 þ regulatory T-cell population and a decreased macrophage candidacidal capacity in the presence of TLR2. These findings were supported by Bellocchio et al, 78 who found a reduced fungal load in the kidneys of TLR2-deficient mice but no difference in mortality. The reason for the apparently opposing role of TLR2 in controlling the response to systemic candidiasis is unclear, but may reflect differences in the strain of C. albicans used, since TLRs have been shown to discriminate between fungal morphotypes.…”
Section: Deficiencies Of Innate Immunity and Involvement In Early Infsupporting
confidence: 70%
“…The reason for the apparently opposing role of TLR2 in controlling the response to systemic candidiasis is unclear, but may reflect differences in the strain of C. albicans used, since TLRs have been shown to discriminate between fungal morphotypes. 32,78 The mannose receptor is another pattern recognition receptor that was thought to recognize C. albicans through the binding of specific cell wall glycans, based on in vitro studies. 79,80 However, a recent study in mannose receptor knockout mice showed no significant difference in overall susceptibility compared to wildtype controls, 81 suggesting that this is not a major receptor for C. albicans detection, or that a redundancy exists with the TLR4/CD14 system.…”
Section: Deficiencies Of Innate Immunity and Involvement In Early Infmentioning
confidence: 99%
“…Zymosan and fungal pathogens like C. albicans and A. fumigatus are sensed by TLR2 that signals via myeloid differentiation factor 88 (MyD88), resulting in NF-jB activation and the production of cytokines [10][11][12][13]. The importance of this signaling cascade can be inferred from the fact that MyD88-knockout mice show an increased susceptibility to fungal infections [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Zymosan and fungal pathogens like C. albicans and A. fumigatus are sensed by TLR2 that signals via myeloid differentiation factor 88 (MyD88), resulting in NF-jB activation and the production of cytokines [10][11][12][13]. The importance of this signaling cascade can be inferred from the fact that MyD88-knockout mice show an increased susceptibility to fungal infections [14,15].Dectin-1 is expressed on myeloid cells like macrophages, neutrophils, monocytes, and even a subset of T cells [16]. Dectin-1 mediates fungal recognition and Revised 2/11/07 Accepted 11/12/07 [DOI 10.1002/eji.200737647] Key words: Antigen presentation Á Dendritic cell Á Fungal Á T cell Abbreviations: b2m: b2-microglobulin Á Dectin-1: DC-associated C-type lectin-1 Á CR3: complement receptor 3 Á MR: mannose receptor Á SIGNR1: ICAM-3-grabbing nonintegrin (DC-SIGN) homolog, SIGN-related 1 uptake by binding b-glucans [7,9,17,18], which are conserved cell wall components of fungi and some bacteria.…”
mentioning
confidence: 99%
“…9,10 Components of the neutrophil microbicidal system, including NADPH oxidase and myeloperoxidase protect against infection, 11,12 while members of the Toll-like receptor (TLR) family appear to have disparate effects on infection outcome. [13][14][15][16] A T helper (Th)1-type response has been shown to be protective against reinfection with C. albicans, while a Th2 response is more frequently observed in susceptible strains. 17 Additionally, C. albicans has been shown to activate the complement system through the alternative pathway, 18 with the chemotactic and inflammatory activities of complement apparently the crucial components for mounting an effective host defence.…”
Section: Introductionmentioning
confidence: 99%